JORDAN AND GULF CRISIS - Dr. Riyad Mofleh AL-Khlaifat, Dr. Ali Ibarheem Albashayreh, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In the present Iraq-Kuwait conflict and Gulf war. Jordan supported Iraq. Jordan's unequivocal backing for Iraq was the result of a special relationship that was first developed in the late 1970's (1). For the last one decade this link made Jordan economically. Politically and militarily dependent on Iraq. In this Chapter an attempt has been made to discuss the Jordan's role in the Gulf Crisis and reasons for its supporting Iraq in the Iraq-Kuwaitwar.